Comparison of results of continuum and finite element models on large diameter SFRC tunnel liner performance in local ground conditions - Lei, Ao (Nanyang Technological University, 2023)
The high population density in Singapore has led to increased demand for infrastructure, prompting the use of underground space utilization. Singapore has constructed large diameter MRT tunnels with Steel Fibre Reinforced Concrete (SFRC) for its improved performance. Engineers involved in many projects with small diameter tunnels realize the limitations of the conventional Muir Wood Method when designing the larger diameter tunnels surrounded by multi-layered soil. Although the conventional method widely accepted by many engineers results in a conservative design, it is necessary to study whether this method can be still valid when the multi-layered soil and larger diameter tunnel is applied. This project aimed to analyze the effects of different ground conditions in Singapore on the displacement, hoop stress and bending moment distribution of 12m SFRC tunnel liners using both continuum model calculation and finite element model simulation. Three 2D models correspond to different locations with typical soil conditions on the tunnel construction route of an ongoing MRT project with a large-diameter single bored tunnel were developed. The study compares the Muir Wood and Curtis Method (continuum model) calculated by MATLAB with the finite element model generated by Plaxis 2D, and provides recommendations for the optimum parameter values for the continuum model calculation. The results suggest that engineers can achieve more economical designs by using FS=1.2 instead of 1.4 and, for tunnels buried in very soft soils, using the average soil’s elastic modulus E and adopting K up to 0.8. In summary, this project highlights the need to use both continuum and finite element methods for design to achieve the best balance of safety and economy for large diameter SFRC tunnels.